IMPLEMENTASI METODE REGRESI LINIER PADA PERTUMBUHAN DAN HASIL PANEN JAGUNG MANIS TERHADAP PEMBERIAN PUPUK HAYATI PADAT - Ulya, Zahratul (Universitas Malikussaleh, 2025)
This study aims to analyze the effect of solid biofertilizer application on sweet corn yield using a multiple linear regression prediction model. The growth and yield of sweet corn are greatly influenced by the availability of adequate and balanced nutrients in the soil. Biofertilizer was chosen as an environmentally friendly alternative to reduce dependence on chemical fertilizers. Three doses of biofertilizer were tested, namely P0 (0 kg/ha), P1 (60 kg/ha), and P2 (120 kg/ha). Linear regression analysis was used to examine the relationship between biofertilizer dosage and growth, as well as the contribution of growth to yield. The results of the analysis showed that the P1 dose gave the best results for all parameters observed, including the weight and length of corn cobs, both with and without husks. The P0 dose produced the lowest values for all variables due to minimal nutrient intake, while the P2 dose showed a decrease in yield compared to P1, indicating a possible effect of nutrient saturation. Thus, a dose of 60 kg/ha (P1) was identified as the optimal dose for increasing sweet corn productivity under the conditions of this study. This proves that linear regression can be used as a tool to predict crop yields based on biological fertilizer doses, thereby helping farmers determine the optimal dose to increase sweet corn productivity in a sustainable manner. Kata kunci: sweet corn, solid biofertilizer, fertilizer dose, yield, linear regression